2021
DOI: 10.1002/alz.12526
|View full text |Cite
|
Sign up to set email alerts
|

How good are medical and death records for identifying dementia?

Abstract: Introduction:Retrospective studies using administrative data may be an efficient way to assess risk factors for dementia if diagnostic accuracy is known. Methods: Within-individual clinical diagnoses of Alzheimer's disease (AD) and allcause dementia in ambulatory (outpatient) surgery, inpatient, Medicare administrative records and death certificates were compared with research diagnoses among participants of Cache County Study on Memory, Health, and Aging (CCSMHA) (1995-2008, N = 5092).Results: Combining all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Further research that takes into account confounding of the exposure–mediator relationship and of the mediator–outcome relationship is warranted. Second, we recognize that using administrative health‐care records for dementia ascertainment may result in misclassification, especially in underdetection of dementia 41 . Worldwide there are barriers to receiving a diagnosis of a dementing disease, 48 an inherent limitation of studying dementia that impacts all research in this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research that takes into account confounding of the exposure–mediator relationship and of the mediator–outcome relationship is warranted. Second, we recognize that using administrative health‐care records for dementia ascertainment may result in misclassification, especially in underdetection of dementia 41 . Worldwide there are barriers to receiving a diagnosis of a dementing disease, 48 an inherent limitation of studying dementia that impacts all research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…We further classified dementia as AD, vascular dementia, or other/unspecified dementia including frontotemporal dementia, dementia with Lewy bodies, or all others. Our prior research indicates that UPDB administrative health records from 1996 to 2008 have 71% sensitivity and 81% specificity for all‐cause dementia diagnoses compared to gold‐standard research diagnoses 41 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…International variations in the recording of dementia or AD as the UCOD can be further divided into variations in the underreporting of dementia or AD as a COD and variations in the recording of dementia or AD in part I of a death certificate. Several cohort studies have identified an underreporting of dementia or AD as a COD on death certificates 26–31 . Physicians in hypothetical countries A through C were more likely than those in Country D to diagnose AD as the COD.…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies have identified an underreporting of dementia or AD as a COD on death certificates. [26][27][28][29][30][31] Physicians in hypothetical countries A through C were more likely than those in Country D to diagnose AD as the COD. Furthermore, physicians in hypothetical countries A and B were more likely than those in Country C to record AD in the death certificate resulting in higher recorded AD mortality rates in countries A and B (Fig.…”
Section: With Regard To the Timely Diagnosis Of Dementia And Ad Globa...mentioning
confidence: 95%